2022
DOI: 10.1177/13623613221138691
|View full text |Cite
|
Sign up to set email alerts
|

Short report: A co-designed psychoeducation for older autistic adults-a multiple case study

Abstract: There are currently no old-age specific interventions for autistic adults. Therefore, in this explorative study, we examined the possible effects of a co-designed psychoeducation program for older autistic adults (55+ years), with a multiple case study design ( N = 9, age 56–73 years; Netherlands Trial Register (code Trial NL5670)). For each participant, also a person close to them (a proxy) participated. This allowed us to calculate a discrepancy score regarding autistic traits and cognitive challenges. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…For example, the utility of therapies for anxiety and depression (e.g., Cognitive Behavioral Therapy, Dialectical Behavioral Therapy, and Mindfulness approaches) has been examined in samples including autistic adults [ 127 , 129 , 130 ] but has not yet been specifically examined in older autistic adults. Research is also needed to examine psychoeducational interventions for older adults [ 131 ] and self-care practices [ 132 ] as avenues for intervention with older autistic adults.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the utility of therapies for anxiety and depression (e.g., Cognitive Behavioral Therapy, Dialectical Behavioral Therapy, and Mindfulness approaches) has been examined in samples including autistic adults [ 127 , 129 , 130 ] but has not yet been specifically examined in older autistic adults. Research is also needed to examine psychoeducational interventions for older adults [ 131 ] and self-care practices [ 132 ] as avenues for intervention with older autistic adults.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of the study, the effectiveness of customized psychoeducation for older autistic adults was still being studied. 21 Additionally, the study suggested that complementary mediational therapy can be beneficial, involving a role for home care institutions or other (in)formal caregivers. There is a significant overlap in behavior characteristic of both ASD and BPSD.…”
Section: Dealing With Asd In Nursing Homesmentioning
confidence: 98%
“…However, the AQ-28 is not recommended for this purpose as it is a selfreport questionnaire and therefore not suitable for administration to individuals with dementia or BPSD. 21…”
Section: Recognizing Asd In Late Lifementioning
confidence: 99%
See 2 more Smart Citations